2020
DOI: 10.1155/2020/8810813
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells: Current Applications and Future Directions in the Regeneration of Multiple Tissues

Abstract: Adipose-derived stem cells (ADSCs) can maintain self-renewal and enhanced multidifferentiation potential through the release of a variety of paracrine factors and extracellular vesicles, allowing them to repair damaged organs and tissues. Consequently, considerable attention has increasingly been paid to their application in tissue engineering and organ regeneration. Here, we provide a comprehensive overview of the current status of ADSC preparation, including harvesting, isolation, and identification. The adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 188 publications
2
101
0
1
Order By: Relevance
“…Recent studies have demonstrated that the effectiveness of ADSCs in regenerative medicine is due to their paracrine effects [ 13 ]. Thus, ADSCs have been identified as new therapeutic agents in biomedicine [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that the effectiveness of ADSCs in regenerative medicine is due to their paracrine effects [ 13 ]. Thus, ADSCs have been identified as new therapeutic agents in biomedicine [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the expression of CD36 and lack of CD106 distinguish ASCs from bone marrow MSCs [74]. However, there is still a lack of consensus in definitive markers that discriminate ASCs [79], because surface biomarkers differ depending on donor sites and culture procedure [80].…”
Section: Ascs and The Regenerative Property Of Fat Graftingmentioning
confidence: 99%
“…It is well documented that adipose-derived mesenchymal stem cells (ADSCs) have multilineage differentiation potential and can differentiate into different cell types, including adipocytes, osteoblasts, chondrocytes, and hepatocytes [ 10 ]. ADSCs can also repair damaged organs and tissues through releasing a variety of paracrine factors and extracellular vesicles (EVs) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%